Hubungan Antara Dukungan Suami dengan Pemberian Asi Eksklusif - Salma Qurrata A’yun; Enny Yuliaswati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Breast milk is the first natural food for babies which contains vitamins, minerals and nutrients that babies need for growth in the first six months, and no other food or liquid is needed. Data on exclusive breastfeeding in Indonesia in 2023 is around 73.9%, this figure still does not meet the national exclusive breastfeeding target of 80%. Family support factors, including the husband, greatly determine success in breastfeeding, because family influence influences the mother's emotional state, which indirectly also influences breast milk production. Objective: to determine the relationship between husband's support and exclusive breastfeeding. Method: quantitative research using analytical survey methods with a cross sectional approach. Sampling using the Slovin formula obtained 31 respondents with the criteria of mothers who have babies aged 6-12 months. Results: The results of this research prove that there is a relationship between husband's support and exclusive breastfeeding based on the chi square test which shows an Asymp.Sig value of 0.000 which is smaller than 0.05. Conclusion: there is a relationship between husband's support and exclusive breastfeeding.